Remote electrical neuromodulation (REN) wearable device for adolescents with migraine: a real-world study of high-frequency abortive treatment suggests preventive effects - Monteith, Teshamae S.; Stark-Inbar, Alit; Shmuely, Sharon; Harris, Dagan; Garas, Sandy; Ironi, Alon; Kalika, Paige; Irwin, Samantha L. (Frontiers in Pain Research, 2023)
Introduction Migraine is a chronic neurological disease manifesting as attacks of disabling head pain and associated symptoms. Remote electrical neuromodulation (REN) is a non-pharmacological, prescribed, wearable device (Nerivio®). This device has been certified by the FDA for the acute and/or preventive treatment of migraine with or without aura in patients 12 years of age or older. The device is affixed to the user’s arm during 45-min treatment sessions and is operated using a smartphone app. This study (NCT05769322) aims to evaluate whether frequent use of REN for the acute treatment of migraine in adolescents resulted in a reduction in monthly migraine treatment days (MMTD), as previously demonstrated in adults through a dedicated prevention clinical trial (NCT04828707). Methods The study included real-world prospective data from adolescent patients who used REN on at least 10 days every 28-day month, following the REN migraine prevention guideline of an every-other-day pattern. Additional requirements were at least three REN treatment days in each of the two subsequent months. The number of MMTD was used as a proxy measure for the number of monthly migraine days (MMD). The change in MMTD from the first month, taken as a “baseline,” to each of the following months was used to evaluate the presence and size of potential migraine preventive benefits of REN in adolescents. Results A total of 83 adolescents were eligible for analysis. The users were 15.9 ± 1.3 years of age (mean ± SD), and 89% of them were female. The results demonstrated a substantial month-to-month reduction in the mean (±SD) number of REN treatment days from 12.6 (±3.2) MMTD in the first month to 9.0 (±4.8) MMTD in the second month (p < 0.001), and a further decrease to 7.4 (±4.2) MMTD in the third month (p < 0.001). This indicates an accumulative reduction of 5.2 (±4.8) mean REN MMTD from the first month to the third month of consecutive REN treatment. The users also reported consistent 2-h acute pain responses in at least 50% of their treated attacks, with 61.9% of the users reported experiencing pain relief, 24.5% reported pain freedom, 67.4% indicated relief in functional disability, and 41.3% reported complete freedom from functional disability. Conclusion The frequent use of REN among adolescents as an acute treatment for migraine attacks resulted in a decrease in the mean number of monthly treatment days in the subsequent months, suggesting that REN may have potential preventive benefits for migraine in this subpopulation.